(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Metal matrix composites have attracted a lot of attention in the recent years due to their excellent properties in different applications. In this study, aluminum metal matrix composites reinforced with different weight percentage(1,2,3,5,7,10%) from alumina and silicon carbide have been preparing by using stir casting. A finite element modeling using ANSYS software is used to model aluminum metal matrix composites. Image processing and image analysis are used based upon image J program to transform the image into engineering geometry that is used in the finite element modeling of metal matrix composites. Static and thermo mechanical analysis have been done for each models to know the response of mechanical stresses and thermal residual stresses on prepared composites.